Tradition and modernization: dialectical tensions in creative religious practices of the Sundanese urban communities - Zayadi, Zayadi (Creativity Studies, 2023)
This study focuses on the religious construction of Sundanese urban communities in the city of Bandung, West Java, Indonesia, which is characterized by dialectical tensions between the need to preserve tradition and the desire to adapt to modernization. These tensions have led to the emergence of various forms of creative and ambiguous religious and cultural practices. The study is based on ethnographic research conducted among the Sundanese urban communities in Bandung, using literature documentation, observations, and interviews as data collection methods. The study findings reveal that the religious practices of Sundanese urban communities are shaped by the diverse elements of urban life. The religious practices are ambiguous due to the dialectical tensions between preserving tradition and adapting to modernization, rationality and irrationality, personal freedom and communal identity, and cultural wisdom values and exclusive Islamic teachings. The unique urban-cultural religious phenomena, such as urban Sufism, hijra (South Asia) movements, religious-identity politics, or the preservation of Sundanese cultural rites with Islamic content, are examples of the religious creativity that emerges as a result of the communities’ understanding of the application of faith in the midst of ideological cultural traditions and pragmatic interests. The study results offer a sociological perspective on the modern life of Sundanese urban communities, where the application of theological-traditional values of religious teachings and pragmatic-modern values of urban life leads to creative constructions.